Habitat and seasonal effects on the nutrient status of selected roan (Hippotragus equinus) and sable antelope (Hippotragus niger) populations in South Africa - Webb, E.C. (Edward Cottington) (University of Pretoria, 2013)
Dissertation (MScAgric)--University of Pretoria, 2009.